Peran Mediator dalam Perdamaiaan Kasus Perceraian di Pengadilan Agama Makassar : Analisis Hukum Islam dan Implementasi Perma No. 1 Tahun 2016: The Role Of Mediators In Peaceful Divorce Cases In The Makassar Religious Court: Analysis Of Islamic Law And Implementation Of Perma No. 1 Of 2016 - satriani satriani; Hambali Husaini (Institut Agama Islam Negeri Fattahul Muluk Papua, 2026)
This study aims to comprehensively analyze the role of mediators in resolving divorce cases at the Makassar Class 1A Religious Court from an Islamic legal perspective and examine the factors that contribute to the success and failure of mediation based on sharia principles. The study uses an empirical normative legal method with a statute approach and a conceptual approach. Primary legal sources include PERMA No. 1 of 2016, Law No. 1 of 1974, Law No. 7 of 1989, the Compilation of Islamic Law, and related MUI Fatwas. Secondary sources include fiqh books (Al-Mughni, Bidāyat al-Mujtahid), scientific journals, and data from Makassar Religious Court decisions from 2021-2023. Data collection was conducted through in-depth interviews with mediator judges, employee mediators, and the parties to the case, as well as document studies. The analysis uses the theory of maqāṣid syarī'ah (especially ḥifẓ al-nasl and ḥifẓ al-nafs), maslaḥah mursalah, and sadd al-dzarī'ah. The study found three main findings. First, the stages of mediation in the Makassar Religious Court include pre-mediation (in accordance with QS. An-Nisa: 35 concerning the appointment of hakamain), the mediation process with a reframing approach and religious counseling, and the preparation of a peace deed. Second, the factors for the success of mediation according to Islamic law are the competence of the mediator as a just hakam, the good faith of the parties (husn al-niyyah), and a psychological-sociological approach that maintains the family's welfare. Third, the factors for failure include a strong desire for divorce due to sharia reasons (continuous disputes, domestic violence, nusyuz), absence without a valid reason (lack of good faith), and the limited number of certified mediators. The success rate of mediation at the Makassar Religious Court is only around 10-15% of the total cases mediated (2021-2023).